Electronic focusing of the ultrasonic beam by means of an annular array system - T. WASZCZUK; T. KUJAWSKA; J. C. SOMER (Archives of Acoustics)
In conventional mechanical contact scanners the lateral resolution is inferior to the axial one. Improving the lateral resolution over a wide range of depth requires the use of a variable focusing system. We choose the phase annular array system which may be used in obstetrics and gynaecology. Calculations of the acoustical pressure were performed assuming pulse excited transducers. For the transmission the range of examination was divided into five focal zones. During reception the system permits dynamic focusing. Measurements of the ultrasonic beam were carried out. These results are in good agreement with calculations and indicate a considerable increase in the lateral resolution.